Etik Liderlik Anlayışının Örgütsel Bağlılığa Etkisi: Kamu Kurumlarında Bir Araştırma - TURAN TORUN, Burcu (Journal of Business Research - Turk, 2023)
Purpose -The purpose of this study is to determine the effect of ethical leadership understanding on organizational commitment. In this context, it is aimed to determine the effects of ethical leadership on emotional commitment, continuance commitment and normative commitment. Design/Methodology/approach - In this study, Smart PLS program was used to determine the relationship between variables. Questionnaire form was used as data collection method in the research. Van province public institutions were chosen as the main mass. The total number of employees working in public institutions in the İpekyolu district of Van is 500. The number of samples to be obtained from this number is calculated as 217. In total, the number of distributed questionnaires was 300, the number of returned questionnaires was 264, and the number of questionnaires subject to analysis was 237. The survey consists of three parts. Demographic variables are in the first part, Ethical Leadership Scale is in the second part, and Organizational Commitment Scale is in the third part. Findings - According to the findings, it was seen that ethical leadership understanding has a significant effect on organizational commitment. Ethical leadership approach is most effective on emotional commitment sub-dimension. It can be said that the ethical leader tries to make the employees see themselves as a part of the business through the ethical values he adopts and the ethical behaviors he displays. In other words, it can be said that as ethical behaviors increase, emotional commitment will increase and managers try to reach their goals by having positive feelings towards the company with such behaviors. It has been determined that ethical leadership affects affective commitment the most among the dimensions of organizational commitment and affects continuance addiction the least. Discussion - The findings of this study that ethical leadership has a significant effect on organizational commitment support the literature. In this direction, it can be said that as ethical behaviors increase, emotional commitment increases and it can be suggested that employees can engage in ethical leadership behaviors in order to increase their organizational commitment.